The personality of an entrepreneur : a psychobiography of Steve Jobs - Ndoro, Tinashe T R (Rhodes University, Faculty of Commerce, Rhodes Business School, 2014)
From Integrative Summary: There has been a growing interest in successful entrepreneurs. Research on entrepreneurship has focused on the identification of personality variables that would assist in the prediction of entrepreneurial success. The present study moves away from attempting to predict entrepreneurial success and instead focuses on exploring and describing the personality of a successful entrepreneur. A psychobiographical case study was adopted by the researcher to explore and describe the extent to which Steve Jobs demonstrated the entrepreneurial characteristics identified by Rauch and Frese (2007). A personality trait approach to entrepreneurship was adopted in the study. The study also attempted to explore the socio-cultural and economic context within which Jobs practised his entrepreneurial activities. Jobs was a successful entrepreneur who co-founded Apple and founded NeXT and Pixar, which were all companies that transformed various technological industries. His entrepreneurial orientation allowed him to produce innovative products that transformed society in various sectors which included personal computing, mobile phones, music, retail stores and films (Isaacson, 2011). A qualitative approach was adopted in the study. The data collection and analysis was guided by the three linked sub-processes proposed by Miles and Huberman (2002) which involved data reduction, data display and conclusion drawing and verification. The findings of this study showed that Jobs demonstrated, at varying levels, all the entrepreneurial characteristics identified by Rauch and Frese (2007) which included a need of achievement, risk-taking, innovativeness, autonomy, locus of control and self-efficacy. The researcher however noted that the desire for autonomy, risk-taking, innovativeness and self-efficacy were the most dominant characteristics driving his entrepreneurial orientation. The research thesis adopted the structure of a teaching case which can be used to explore and discuss the personality trait perspective to entrepreneurship in a classroom setting. The findings of the study can be recognised as positively contributing to the growing field of psychobiographical research on exceptional individuals, including entrepreneurs. The study can be considered as a foundation for future studies which will add to the body of knowledge relating to entrepreneurship and personality.
Keywords: Jobs, Steve, 1955-2011 -- Psychology; Personality assessment; Psychology -- Biographical methods; Businesspeople -- Psychology; Psychohistory; Entrepreneurship -- United States; Businesspeople -- United States